2015
DOI: 10.24218/msear.2015.03
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties Evolutions for Hard Magnetic MnAl and MnGa Based Alloys Prepared by Melt Spinning or Mechanical Milling

Abstract: Mn-based alloys are generally thought to be the potential rare earth free permanent magnets with acceptable magnetic properties due to its available high magnetization and anisotropy field. In this work, MnAl and MnGa based alloys have been investigated regarding to their processing, structures and magnetic properties. MnAl based alloys with various C additions and/or trace rare earth doping were prepared by melt spinning. The phase transitions during rapid quenching and post annealing were investigated. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…2(a,b)) and after conventional annealing for 30 min at 500 C, we obtain single s-phase. The transformation is not completed when lower dwelling times are used, consistent with the literature [18,[27][28][29]. By increasing the temperature to 550 C , one can obtain single s-phase in 5 min with conventional annealing.…”
Section: Resultssupporting
confidence: 84%
“…2(a,b)) and after conventional annealing for 30 min at 500 C, we obtain single s-phase. The transformation is not completed when lower dwelling times are used, consistent with the literature [18,[27][28][29]. By increasing the temperature to 550 C , one can obtain single s-phase in 5 min with conventional annealing.…”
Section: Resultssupporting
confidence: 84%
“…Annealing above 500 °C was not performed in this study because of the reduction in the ferromagnetic τ-phase as already reported for annealing temperatures ≥ 550 °C. 26,27 The XRD patterns for MnAl_400_1h and MnAl_400_2h films annealed for different times are shown in Fig. 3 , which revealed that the τ (100) and τ (101) peaks present in the MnAl_400_1h film were diminished in the MnAl_400_2h film.…”
Section: Resultsmentioning
confidence: 98%
“… 25 On further increasing the temperature from 550 °C to 600 °C, the τ-phase decomposed into non-magnetic γ and β phases. 26,27 Previous studies revealed that ferromagnetic ordering was enhanced in the MnAl thin films on increasing the annealing temperature to 500 °C. 27,28 Therefore, we selected the temperature range from 300 to 500 °C to achieve the desired ferromagnetic phase.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cryo milling increases the potential capability of aligning the crystals along the easy magnetization axis, without the creation of sheet-like particles with random orientation, as previously observed when milling is done at ambient temperatures 25 , 28 . However, for this to be a viable route, single crystal grains (or particles with correspondingly aligned grains) are necessary.…”
Section: Resultsmentioning
confidence: 74%